2019
DOI: 10.1002/mc.23012
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor promotes progression of cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a keratinocyte‐derived invasive and metastatic tumor of the skin. It is the second‐most commonly diagnosed form of skin cancer striking 200 000 Americans annually. Further, in organ transplant patients, there is a 65‐ to 100‐fold increased incidence of cSCC compared to the general population. Excision of cSCC of the head and neck results in significant facial disfigurement. Therefore, increased understanding of the mechanisms involved in the pathogeneses of cSCC coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The expression of CDC258 and CDC25C was increased in cSCC compared to normal skin ( p ≤ 0.001) and led to the suppression of apoptosis in cSCC cells by stimulating Pl3K/Akt signaling and survivin expression [ 18 ]. FGFR2 activation and protein expression was increased in cSCC cells and found to be low in premalignant lesions and normal skin [ 19 ]. In a large study which sought to identify genetic variants in the HLA class II region associated with the risk of cSCC, the authors found that cSCC risk was associated with rs28535317 (OR = 1.20, p = 9.88 × 10 −11 ), which corresponded to an amino-acid change from phenylalanine to leucine at codon 26 of HLA-DRB1 (OR = 1.17, p = 2.48 × 10 −10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CDC258 and CDC25C was increased in cSCC compared to normal skin ( p ≤ 0.001) and led to the suppression of apoptosis in cSCC cells by stimulating Pl3K/Akt signaling and survivin expression [ 18 ]. FGFR2 activation and protein expression was increased in cSCC cells and found to be low in premalignant lesions and normal skin [ 19 ]. In a large study which sought to identify genetic variants in the HLA class II region associated with the risk of cSCC, the authors found that cSCC risk was associated with rs28535317 (OR = 1.20, p = 9.88 × 10 −11 ), which corresponded to an amino-acid change from phenylalanine to leucine at codon 26 of HLA-DRB1 (OR = 1.17, p = 2.48 × 10 −10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The FGF receptor family consists of four members (FGFR-1, FGFR-2, FGFR-3 and FGFR-4), which are mainly involved in collagen synthesis [44,45]. Dysregulation of FGFRs' functions seems to be involved in numerous cancers; evidence indicates that FGF contributes to cSCC development [46].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor receptor (FGFR) is over-expressed in cSCC samples when compared to normal skin and pre-malignant lesions 18 ; moreover, cSCC cells also over-express FGF10, an FGFR binding ligand. Inhibition of FGFR by pan-FGFR inhibitor, AZD4547, decreases tumor growth in immunocompromised mice injected with SCC12 cells.…”
Section: Receptor Tyrosine Kinase Signalingmentioning
confidence: 99%